Nanoscopic Porous Iridium/Iridium Dioxide Superstructures (15 nm): Synthesis and Thermal Conversion by In Situ Transmission Electron Microscopy. Issue 47 (1st August 2019) - Pappert, Kevin; Loza, Kateryna; Shviro, Meital; Hagemann, Ulrich; Heggen, Marc; Dunin‐Borkowski, Rafal E.; Schierholz, Roland; Maeda, Takuya; Kaneko, Kenji; Epple, Matthias
Abstract: Porous particle superstructures of about 15 nm diameter, consisting of ultrasmall nanoparticles of iridium and iridium dioxide, are prepared through the reduction of sodium hexachloridoiridate(+IV) with sodium citrate/sodium borohydride in water. The water‐dispersible porous particles contain about 20 wt % poly( N ‐vinylpyrrolidone) (PVP), which was added for colloidal stabilization. High‐resolution transmission electron microscopy confirms the presence of both iridium and iridium dioxide primary particles (1–2 nm) in each porous superstructure. The internal porosity (≈58 vol%) is demonstrated by electron tomography. In situ transmission electron microscopy up to 1000 °C under oxygen, nitrogen, argon/hydrogen (all at 1 bar), and vacuum shows that the porous particles undergo sintering and subsequent compaction upon heating, a process that starts at around 250 °C and is completed at around 800 °C. Finally, well‐crystalline iridium dioxide is obtained under all four environments. The catalytic activity of the as‐prepared porous superstructures in electrochemical water splitting (oxygen evolution reaction; OER) is reduced considerably upon heating owing to sintering of the pores and loss of internal surface area. Abstract : Interior design : Porous particle superstructures consisting of iridium and iridium dioxide were prepared by reduction of sodium hexachloridoiridate. The three‐dimensional organization of the primary nanoparticles inside the spherical superstructure is demonstrated by electron tomography. The highly porous particles have a pronounced catalytic activity in the oxygen evolution reaction.